Well‐posedness and exponential decay for laminated Timoshenko beams with time delays and boundary feedbacks. (3rd November 2017) - Feng, Baowei
Abstract : This paper is concerned with laminated beams modeled from the well‐established Timoshenko system with time delays and boundary feedbacks. By using semigroup method, we prove the global well‐posedness of solutions. Assuming the weights of the delay are small, we establish the exponential decay of energy to the system by using an appropriate Lyapunov functional.